“I don’t want people laughing at me for hiding Jews at my place . . .” The Case of Zdzisław and Halina Krzyczkowski - Jacek Leociak (Zagłada Żydów)
On 25 May 1988 the Commission for the Designation of the Righteous of the Yad Vashem Institute decided to award Zdzisław and Halina Krzyczkowski the medal Righteous Among the Nations on the application of Marian Berland, who was hiding, together with four people, at the Krzyczkowskis’ place during the occupation. In his letter he wrote that “never throughout the entire period did they give us reasons to fear that they would denounce us or throw us out on the street. We survived that horrible time only thanks to them and their help.” However, Berland’s notes written in hiding reveal a totally different picture; the Krzyczkowskis are a couple of lumpenproletarians from Sienna Street, who constantly cheat and blackmail the Jews they are hiding